Electric‐Field‐Controlled Phase Transformation in WO3 Thin Films through Hydrogen Evolution. Issue 46 (23rd October 2017) - Wang, Meng; Shen, Shengchun; Ni, Jinyang; Lu, Nianpeng; Li, Zhuolu; Li, Hao‐Bo; Yang, Shuzhen; Chen, Tianzhe; Guo, Jingwen; Wang, Yujia; Xiang, Hongjun; Yu, Pu
Abstract: Field‐effect transistors with ionic‐liquid gating (ILG) have been widely employed and have led to numerous intriguing phenomena in the last decade, due to the associated excellent carrier‐density tunability. However, the role of the electrochemical effect during ILG has become a heavily debated topic recently. Herein, using ILG, a field‐induced insulator‐to‐metal transition is achieved in WO3 thin films with the emergence of structural transformations of the whole films. The subsequent secondary‐ion mass spectrometry study provides solid evidence that electrochemically driven hydrogen evolution dominates the discovered electrical and structural transformation through surface absorption and bulk intercalation. Abstract : Using ionic‐liquid gating, a field‐induced insulator‐to‐metal transition is achieved in WO3 thin films with the emergence of structural transformations of the whole films. Subsequent secondary‐ion mass spectrometry provides solid evidence that electrochemically driven hydrogen evolution dominates the discovered electrical and structural transformation through surface absorption and bulk intercalation.